Comparison of the computed tomography values of the bone fragment gap after sagittal split ramus osteotomy in mandibular prognathism with and without asymmetry. Issue 12 (December 2016) - Moroi, A.; Yoshizawa, K.; Iguchi, R.; Kosaka, A.; Ikawa, H.; Saida, Y.; Hotta, A.; Tsutsui, T.; Ueki, K.
Abstract: The purpose of this study was to compare computed tomography (CT) Hounsfield unit values of bone fragment gaps after sagittal split ramus osteotomy (SSRO) in patients with and without asymmetry, and to evaluate differences between the deviated and non-deviated sides in asymmetric patients. Thirty-two patients who underwent a bilateral SSRO were included in this retrospective study. Patients were divided into symmetric and asymmetric groups by cephalometric analysis. CT values of the bone fragment gap were measured at 1 week and at 1 year after surgery. There were significant differences between CT values obtained at 1 week and at 1 year after surgery for all measurement points. However, there were no significant differences in CT values between symmetric and asymmetric patients at either 1 week or 1 year after surgery. Among asymmetric patients, there were no significant differences between the deviated and non-deviated sides at 1 week or 1 year after surgery. This study showed ossification of the bone fragments and adaptation to change the mandible form in patients with and without asymmetry following SSRO.